Mussel-inspired waterproof and self-healing polyurethane with enhanced mechanical properties. (5th October 2021) - Liu, Yahao; Zheng, Jian; Zhang, Xiao; Li, Ke; Zhang, Yu; Du, Yongqiang; Yu, Guibo; Jia, Yunfei
Graphical abstract: Highlights: The mussel-inspired polyurethane with self-healing and waterproof properties were successfully synthesized. The self-healable polyurethane exhibits rapid room-temperature self-healing ability. The self-healable polyurethane possesses excellent waterproof property. The self-healable polyurethane shows remarkable deformation recovery properties, tear-resistance, and toughness. Abstract: Polyurethane-based devices always suffer from complex environment during their service life. Therefore, excellent and well-balanced properties like self-healing, waterproof, and mechanical properties are necessary. Nevertheless, it is challenging and usually contradictory to achieve them simultaneously. In this work, a series of novel mussel-inspired graphene oxide/polyurethane composites were designed and successfully synthesized. The composites show high stress ( η1 ) and strain ( η2 ) self-healing efficiency of 87% and 91% respectively, while their tensile strength is increased by 84% with a high strain of 2190% at the same time. Especially, the self-healing properties were hardly affected after the soaking experiment, determining the outstanding waterproof behavior. Additionally, the composites also possess preferable tear-resistance and toughness. Even cut with a 2 mm width notch, they could still bear the high strain of 1152%. More importantly, the composites also show remarkable deformation recovery properties under both cyclic tensile and compressive loads. It is expected that this polyurethane may be potentially applied in solid propellants, protective coating, electronic skin, soft sensors, and other devices.